2007
DOI: 10.1093/her/cym035
|View full text |Cite
|
Sign up to set email alerts
|

The forgotten dimensions in health education research

Abstract: This paper evaluates the content focus of health education research as presented in the professional literature over a 6-year period (2000-2005). The majority of research (1365 papers) addresses the physical dimension of health (79%), while other health dimensions receive less attention. It is argued that the current content focus of research in health education fails to harmonize with the multidimensional, dynamic and functional nature of health as generally defined. The goal of health education, positive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…The main purpose of this descriptive, quantitative research study was to examine the relationship among the independent variables of existential and religious spirituality with the dependent variable, QOL, among individuals with amputation. The results revealed that a significant correlation existed 6,18,28,29 DHP, Duke Health Profile; 11,15,22 CHART, Craig Handicap Assessment Reporting Technique. between existential spirituality and the Satisfaction with Life Scale (r ¼ 0.73, p < 0.01).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The main purpose of this descriptive, quantitative research study was to examine the relationship among the independent variables of existential and religious spirituality with the dependent variable, QOL, among individuals with amputation. The results revealed that a significant correlation existed 6,18,28,29 DHP, Duke Health Profile; 11,15,22 CHART, Craig Handicap Assessment Reporting Technique. between existential spirituality and the Satisfaction with Life Scale (r ¼ 0.73, p < 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…14 Medical education of clinicians in the 20th century is grounded in the Cartesian model, based on a rigid mindbody separation. 15 Most clinicians do not receive education on spiritual assessment, and the inclusion of spirituality and religion in patient care is rare. 16,17 Despite research reporting that Americans believe that spirituality plays an important role in their health and QOL, the biomedical model of medicine has neglected the existential questions and spirituality issues that accompany illness, focusing instead on diagnosis and treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that education can positively affect health. Overall, the goal of education is to enhance health awareness and attitude, which in turn improves the individual's behaviors and promotes health, comfort, and overall performance in all areas of health (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Social determinants are believed to be reasons as to why the prevalence of diabetes is so high among these patients, but there is now a growing argument that emphasizes the interconnectedness of mental and somatic health dimensions [24], with one dimension affecting the state of the other. This relation has been intuitively known for centuries, but unfortunately, modern mental healthcare and physical healthcare are still often working in silos, if not one against the other [25], and with very important, if not tragic consequences in terms of poorer quality of life and shortened lifespan.…”
Section: Introductionmentioning
confidence: 99%